K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 10 2021

\(\left(5x-2y\right)\left(x^2-xy+1\right)\)

\(=5x^3-5x^2y+5x-2x^2y+2xy^2-2y\)

\(=5x^3-7x^2y+2xy^2+5x-2y\)

16 tháng 2 2017

(5x – 2y)( x 2  – xy + 1)

= 5x.( x 2  – xy + 1) – 2y( x 2  – xy + 1)

= (5 x 3  – 5 x 2 y + 5x) – (2 x 2 y – 2x y 2  + 2y)

= 5 x 3  – 5 x 2 y + 5x – 2 x 2 y + 2x y 2  – 2y

= 5 x 3  – 7 x 2 y + 5x + 2x y 2  – 2y

29 tháng 10 2023

`(5x-2y).(x^2 - xy+1)`

`=5x^3 -5x^2y + 5x - 2x^2y + 2xy^2 - 2y`

`=5x^3-7x^2y+2xy^3 +5x -2y`

`(9y^7 -4xy^5 + 5x^2y^4z):(-y)^3`

`=-9y^4 +4xy^2 -5x^2yz`

1 tháng 11 2021

a) \(=\left(x-y\right)\left(x+y\right)-2\left(x-y\right)=\left(x-y\right)\left(x+y-2\right)\)

b) \(=2\left(x+y\right)-x\left(x+y\right)=\left(x+y\right)\left(2-x\right)\)

c) \(=3x\left(x-y\right)+5\left(x-y\right)=\left(x-y\right)\left(3x+5\right)\)

d) \(=\left(x+y\right)^2-25=\left(x+y-5\right)\left(x+y+5\right)\)

e) \(=x\left(x^2-11x+30\right)\)

f) \(=x\left(x-3\right)+6\left(x-3\right)=\left(x-3\right)\left(x+6\right)\)

a: \(\left(\dfrac{1}{3}x+2y\right)\left(\dfrac{1}{9}x^2-\dfrac{2}{3}xy+4y^2\right)=\dfrac{1}{27}x^3+8y^3\)

b: \(\left(x^2-\dfrac{1}{3}\right)\left(x^4+\dfrac{1}{3}x^2+\dfrac{1}{9}\right)=x^6-\dfrac{1}{27}\)

c: \(\left(y-5\right)\left(y^2+5y+25\right)=y^3-125\)

AH
Akai Haruma
Giáo viên
2 tháng 1

Lời giải:
a. $(x+y)-(x-y)=x+y-x+y=(x-x)+y+y=0+2y=2y$

b. $3x(5x^2-2x-1)-15x^3=15x^3-6x^2-3x-15x^3=-6x^2-3x$
c. $(5x-2y)(x^2-xy+1)+7x^2y=5x^3-5x^2y+5x-2x^2y+2xy^2-2y+7x^2y$

$=5x^3+(-5x^3y-2x^2y+7x^2y)+5x+2xy^2-2y$

$=5x^3+5x+2xy^2-2y$

a) Ta có: \(\left(5x-2y\right)\left(x^2-xy+1\right)\)

\(=5x^3-5x^2y+5x-2x^2y+2xy^2-2y\)

\(=5x^3-7x^2y+2xy^2+5x-2y\)

b) Ta có: \(\left(x-1\right)\left(x+1\right)\left(x+2\right)\)

\(=\left(x^2-1\right)\left(x+2\right)\)

\(=x^3+2x^2-x-2\)

c) Ta có: \(\dfrac{1}{2}x^2y^2\cdot\left(2x+y\right)\left(2x-y\right)\)

\(=\dfrac{1}{2}x^2y^2\left(4x^2-y^2\right)\)

\(=2x^4y^2-\dfrac{1}{2}x^2y^4\)